Strength Of Character In Teachers Of Children With Special Needs - Salwa Najiah; Retno Hanggarani Ninin; Fitriani Yustikasari Lubis (Jurnal Indonesia Sosial Teknologi, 2023)
Education is a right for everyone including students with special needs or also called Children with Special Needs (ABK). Teachers must guide and provide learning facilities for their students to achieve educational goals. In the learning process, students categorized as ABK require different services than non-ABK children. Educating ABK is not easy, the strength of the teacher's character is an important factor that can support teachers in dealing with ABK. Strength of character reflects virtue values which refer to positive qualities consisting of good character and are raised by individuals to deal with certain conditions, such as when experiencing difficulties. The study aimed to see an illustration of the strength of character possessed by ABK teachers in educating ABK. This study uses a qualitative approach. The sample in the study numbered two people who were willing to become research participants by collecting data using interview techniques that were conducted online and the data obtained was analyzed thematically. The results showed that the typologies possessed by ABK teachers were creativity, judgment, and teamwork. Even so, each teacher also has several different strengths.